On the merits of, and myths about International Assessments. Issue 4 (19th August 2014) - Pizmony-Levy, Oren; Harvey, James; Schmidt, William; Noonan, Richard; Engel, Laura; Feuer, Michael J.; Braun, Henry; Santorno, Carla; Rotberg, Iris; Ash, Paul; Chatterji, Madhabi; Torney-Purta, Judith
Abstract : Purpose: This moderated discussion appraises popular misconceptions, benefits and limitations of International Large Scale Assessment (ILSA) programs, clarifying how ILSA results could be more appropriately interpreted and used in public policy contexts in the United States (U.S.) and elsewhere in the world. Design/methodology/approach: To bring key issues, points-of-view and recommendations on the theme to light, the method employed is a "moderated policy discussion". Nine commentaries were invited to represent voices of leading ILSA scholars/researchers and measurement experts, juxtaposed against views of prominent leaders of U.S. education systems that participate in ILSA programs. The discussion is excerpted from a recent blog published by Education Week. It is moderated with introductory remarks from the guest-editor and concluding recommendations from an ILSA researcher who did not participate in the original blog. References and author biographies are presented at the end of the article. Findings: Together, the commentaries address historical, methodological, socio-political and policy issues surrounding ILSA programs vis-à-vis goals of education and larger societal concerns. Authors offer recommendations for improving the international studies themselves and reports for educators and the public to facilitate greater understanding of their purposes, meanings, and policy implications. Originality/value: When assessment policies are implemented from the top down, as is often the case with ILSA program participation, educators and leaders in school systems tend to be left out of the conversation. This article is intended to foster a productive two-way dialogue among key ILSA actors that can serve as a stepping stone to more concerted policy actions within and across national education systems.